THE PORT OF TUJU-TUJU IN BONE REGENCY (1990-2015) - Bahtiar, Bahtiar; Asis, Abdul; Hetty, Hetty (Walasuji : Jurnal Sejarah dan Budaya, 2021)
This study aimed to describe the activities of Tuju-Tuju Port in the period of 1990 to 2015. The Tuju-Tuju Port in Bone Regency is a port that transports various commodities produced from several areas in South Sulawesi to other areas, especially to East Nusa Tenggara and its surroundings. The result study showed the activities in Tuju-Tuju Port that the ships going in and out of Tuju-Tuju Port were crowded everyday. Even though the port condition is not yet fully adequate, the loading and loading of goods still continues. The method used was the historical method with analytical descriptive consisting heuristics, source criticism, interpretation, and writing. The Tuju-Tuju Port in Bone Regency is a companion port from other ports in Bone Regency. The Tuju-Tuju Port can affect the local economy, such as increasing regional income and opening up job opportunities for the productive ages. The Tuju-Tuju Port over time has also developed the existing loading and unloading system with simple facilities and infrastructure in Tuju-Tuju Port. Daily activities continue, so the ships that are leaning on the pier and waiting for departure scheduled are crowded adorning the harbor.Â